Menyusun Dokumen Manajemen Supervisi Klinis di SMA Unggul Del Melalui Pendekatan “Sintesis Bukti Terbaik” : Studi Kasus Periode Tahun Ajaran 2021/2022-2022/2023 - Zandroto, Weni; Purba, Sukarman; Zainuddin, Zainuddin (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2024)
The purpose of this study was to develop a concept of clinical supervision management as a guideline for schools. This study aims to develop a clinical supervision management model in superior schools using the